2013
DOI: 10.1103/physrevc.87.045204
|View full text |Cite
|
Sign up to set email alerts
|

Thresholdπ0photoproduction in relativistic chiral perturbation theory

Abstract: We present a calculation of π 0 photoproduction on the proton in manifestly Lorentz-invariant baryon chiral perturbation theory up to and including chiral order q 4 . With the results we analyze the latest π 0 photoproduction data in the threshold region obtained at the Mainz Microtron. In the calculation of observables and the fit of the low-energy constants, we take S, P , and D waves into account. We compare the results for the multipoles with the corresponding single-energy analysis. Furthermore, we also f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 50 publications
5
65
0
Order By: Relevance
“…This is a work in progress but preliminary results are encouraging as our results show a clear improvement from the ∆-less O(p 4 ) heavy baryon and relativistic results published by Fernández-Ramírez et al and Hilt et al respectivley [9,10].…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…This is a work in progress but preliminary results are encouraging as our results show a clear improvement from the ∆-less O(p 4 ) heavy baryon and relativistic results published by Fernández-Ramírez et al and Hilt et al respectivley [9,10].…”
mentioning
confidence: 51%
“…This data was first analysed by Fernández-Ramírez et al in the fourth-order heavy baryon approach [9]. Separately, Hilt et al used the O(p 4 ) relativistic Extended On Mass Shell (EOMS) calculation and found that the HB approach performed slightly better [10]. They concluded that both theories fail to describe the process beyond energies of E γ ≈ 170 MeV.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013 a first measurement of the γp → π 0 p reaction using linear polarised photons and an unpolarised liquid H 2 target was published [10]. Here all P-waves were determined from experiment which allowed a detailed comparison with ChPT [12][13][14].…”
Section: γP → π 0 Pmentioning
confidence: 99%
“…Heavy Baryon Chiral Perturbation Theory (HBChPT) [3,4] and Relativistic Baryon Chiral Perturbation Theory (RBChPT) [5] provide effective parametrizations for low-energy neutral pion photoproduction up to E γ 170 MeV [6,7]. The inclusion of the ∆(1232) resonance as an explicit degree of freedom in RBChPT allows to extend the agreement between theory and data up to E γ 200 MeV [8].…”
Section: Introductionmentioning
confidence: 99%